Genome-Wide Characterization of Superoxide Dismutase (SOD) Genes in Daucus carota: Novel Insights Into Structure, Expression, and Binding Interaction With Hydrogen Peroxide (H2O2) Under Abiotic Stress Condition - Zameer, Roshan; Fatima, Kinza; Azeem, Farrukh; ALgwaiz, Hussah I. M.; Sadaqat, Muhammad; Rasheed, Asima; Batool, Riffat; Shah, Adnan Noor; Zaynab, Madiha; Shah, Anis Ali; Attia, Kotb A.; AlKahtani, Muneera D. F.; et al. (Frontiers in Plant Science, 2022)
Superoxide dismutase (SOD) proteins are important antioxidant enzymes that help plants to grow, develop, and respond to a variety of abiotic stressors. SOD gene family has been identified in a number of plant species but not yet in Daucus carota. A total of 9 DcSOD genes, comprising 2 FeSODs, 2 MnSODs, and 5 Cu/ZnSODs, are identified in the complete genome of D. carota, which are dispersed in five out of nine chromosomes. Based on phylogenetic analysis, SOD proteins from D. carota were categorized into two main classes (Cu/ZnSODs and MnFeSODs). It was predicted that members of the same subgroups have the same subcellular location. The phylogenetic analysis was further validated by sequence motifs, exon–intron structure, and 3D protein structures, with each subgroup having a similar gene and protein structure. Cis-regulatory elements responsive to abiotic stresses were identified in the promoter region, which may contribute to their differential expression. Based on RNA-seq data, tissue-specific expression revealed that DcCSD2 had higher expression in both xylem and phloem. Moreover, DcCSD2 was differentially expressed in dark stress. All SOD genes were subjected to qPCR analysis after cold, heat, salt, or drought stress imposition. SODs are antioxidants and play a critical role in removing reactive oxygen species (ROS), including hydrogen peroxide (H2O2). DcSODs were docked with H2O2 to evaluate their binding. The findings of this study will serve as a basis for further functional insights into the DcSOD gene family.